Clinical Guide for the Use of Metabolic Carts: Indirect Calorimetry—No Longer the Orphan of Energy Estimation. (24th December 2015) - Singer, Pierre; Singer, Joelle
Abstract : Critically ill patients often require nutrition support, but accurately determining energy needs in these patients is difficult. Energy expenditure is affected by patient characteristics such as weight, height, age, and sex but is also influenced by factors such as body temperature, nutrition support, sepsis, sedation, and therapies. Using predictive equations to estimate energy needs is known to be inaccurate. Therefore, indirect calorimetry measurement is considered the gold standard to evaluate energy needs in clinical practice. This review defines the indications, limitations, and pitfalls of this technique and gives practice suggestions in various clinical situations.